Analyzing the Volatility of Non-Core Deposits in Indonesian Islamic Banks: Sharia Restricted Intermediaries Accounts (SRIA) as Stabilizer? - Syamlan, Yaser Taufik; Rahman, Herdi Almadiptha (Universitas Syiah Kuala, 2023)
Objective This research delves into the causes of Non-Core Deposit by applying the Austrian Business Cycle Theory (ABCT) in the case of Islamic Bank. To examine it. This paper is using some internal and external factors in exploring the volatility of Non-Core Deposit in Islamic Bank for both Full-Fledged and Islamic Window Bank. Furthermore, this paper also proposes the future model of Islamic bank using new product namely Sharia Restricted Intermediaries Account (SRIA)Design/methodology The study centers on core deposits as the dependent variable, drawing data from the Indonesian Financial Service Authority and Central Bank of Indonesia websites spanning from June 2014 onwards. This study uses internal variables which are Third-Party Fund, Cost of fund, and Vostro while Conventional Interest Rate and Bank Indonesia Rate as external variables as the independent variable. Methodologically, Vector Auto Regression (VAR) and Vector Error Correction Model (VECM). To propose the future model, this paper do the descriptive analysis.Results The Total Third-Party Funds and Cost of Fund of Conventional Banks exerting significant negative effects to Non-Core Deposit. As a solution, a two-stage implementation plan is proposed: in the short term, separating funds based on purpose and introducing guarantees, while in the long term, introducing Sharia Restricted Intermediaries Account (SRIA) without LPS guarantees to promote stability and risk sharing.Research limitations/implications Understanding the dynamics and future model by all stakeholders can aid in the formulation of policies aimed at fostering a stable and resilient Islamic banking sector. Banks, particularly Islamic banks, can leverage the insights gained from this research to enhance risk management strategies and future innovative products.Novelty/Originality This paper innovatively applies the Austrian Business Cycle Theory to investigate irregular deposits and bank runs in Islamic banks. The finding informs a two-stage plan for stability, aiding policy and risk management.